PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN NASIONAL - Sakir, Moh (IAIN Ponorogo, 2014)
Abstract: Existence of Islamic education have big role in the education history at Indonesia, but the role still havenât full independence itâs political and also its implementation. This matter look by law that formal Islamic education which known by government is Islamic education. Known education is madrasah which have been registered through MAPENDA under Kemenag. Islamic Boarding School still in confession of Moslem society alone which only accepted by Moslem society itself. Therefore Islam people fight not only conducting education but also overall of financing side, education political and independence. Thereby Islamic education require to be improved again by entire all stakeholder Moslem society for the sake of Islamic education as same as Islam aspiration. Appearance of public education system and Islamic education are two sides cannot separate each other in national education system, both related and equipping each other. In the one side the aim of national education is to develop studentâs potency in order to become god-fearing and religious, good manner, healthy, knowable and expected to be democratic citizen and responsible.Ù ÙØ®Øµ: Ø£Ø³ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§Ø³ÙØ§Ù Ø§ ÙØ¨ÙØ±Ø§ ÙÙ ØªØ§Ø±ÙØ® Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§. ÙÙÙÙ ÙØ¬ÙØ¯ÙØ§ ÙÙ ÙÙØ¹Ø· ÙÙØ§ Ø§ÙØ§Ø³ØªÙÙØ§ÙÙØ© Ø§ÙØªØ§Ù Ø© Ø³ÙØ§Ø³ÙØ§ ÙØªØ·Ø¨ÙÙÙØ§. ÙÙØ°Ø§ ÙØ¸ÙØ± ÙØ§ÙÙÙÙØ§ Ø±Ø³Ù ÙØ§ Ø£Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ Ø¹ØªØ±ÙØ© ÙØ¯Ù Ø§ÙØÙÙÙ Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙ ØªÙ ÙØ²Ø© Ø¨Ø§ÙØªØ¹Ø§ÙÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Ø ÙÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ Ø³Ø¬ÙØ© ÙÙ Ù Ø¬ÙØ³ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø³Ø§Ø³ÙØ© ÙÙ ÙØ²Ø§Ø±Ø© Ø§ÙØ´Ø¤ÙÙ Ø§ÙØ¯ÙÙÙØ©. Ø£Ù Ø§ Ø§ÙØ¨Ø³ÙØªØ±ÙÙØ§Øª ÙÙÙ Ù Ø¹ØªØ±ÙØ© ÙØ¯Ù Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ Ø³ÙÙ Ø£ÙÙØ³ÙÙ . ÙØ°Ø§ ÙØ¥Ù Ø¬ÙØ§Ø¯ Ø§ÙÙ Ø³ÙÙ ÙÙ ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ ÙÙÙÙ ÙÙØ·Â ÙÙ ØªØ·Ø¨ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙØØ³Ø¨ ÙÙÙÙ ÙÙ Ø¬Ù ÙØ¹ Ø§ÙØ¬ÙØ§ÙØ¨Ø Ø§ÙØªÙØ§ÙÙÙ ÙØ§ÙØ³ÙØ§Ø³Ø© Ø§ÙØªØ±Ø¨ÙÙØ© ÙØ§ÙØ§Ø³ØªÙÙØ§ÙÙØ©. Ø¨ÙØ°Ø§ ÙØ§Ø¨Ø¯ Ù Ù ØªØ±ÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ ÙØ¬ÙØ¯Ø© Ø¨Ù Ø´Ø§Ø±ÙØ© Ø¬Ù ÙØ¹ Ø§ÙØ´Ø®ØµÙØ§Øª ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹ Ø§ÙÙ Ø³ÙÙ ÙØªÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ù ÙØ§ÙÙØ© Ø¨Ù Ø§ ÙØ±ÙØ¯Ù Ø§ÙØ¥Ø³ÙØ§Ù . ÙØ¸ÙÙØ± Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙØ¹Ø§Ù ÙØ§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ù ÙÙ Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù ÙØ§ ÙÙ ÙÙ ÙØµÙÙÙ Ø§Ø ÙØ£ÙÙÙ Ø§ Ù Ø±ØªØ¨Ø·Ø§Ù ÙÙÙÙ Ø®ØµØ§Ø¦ØµÙ ÙÙ Ù ÙØ²Ø§ØªÙ Ø§ÙÙ ØªÙØ§Ù ÙØªØ§Ù. ÙÙ Ø¬Ø§ÙØ¨ Ø£Ù Ø£ÙØ¯Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙØ·ÙÙØ© ÙÙ ØªÙÙ ÙØ© ÙØ¯Ø±Ø§Øª Ø§ÙØªÙØ§Ù ÙØ° ÙÙÙÙÙÙØ§ Ø£ÙØ§Ø³Ø§ Ù Ø¤Ù ÙÙÙ Ø¨Ø§ÙÙÙ ÙÙ ØªÙÙÙØ ÙÙ ØªØ®ÙÙÙÙ Ø¨Ø£Ø®ÙØ§Ù ÙØ±ÙÙ Ø©Ø Ø£ØµØÙØ§Ø¡ Ø¬Ø³Ù ÙØ§ ÙÙÙÙ Ø¹ÙÙÙ ÙÙØ±Ø¬Ù Ø£Ù ÙÙÙÙÙØ§ Ù ÙØ§Ø·ÙÙÙ Ø£Ù ÙØ§Ø¡ ÙØ¯ÙÙ ÙØ±Ø§Ø·ÙÙÙ.Â Â Â Keywords: Pendidikan Islam, pesantren, madrasah.